The interaction of 9-amine-9-fluorenephosphonic acid derivatives (new morphactins) with some herbicides in toxicity towards Spirodela - Henryk Skrabka; Elżbieta Jaskulska (Acta Agrobotanica, 2013)
Examined was the possibility of interaction between morphactins and herbicides in phytotoxicity towards Spirodela as a test plant. Three newly synthesized 9-amine-9-fluorenephosphonic acid derivatives and the following herbicides were used: Aresin, Banvell D4-S, Gesagard, Pielik, Sys 67-Prop and U-46 KV Pulver. Synergism in phytotoxicity to Spirodela was found in the case of joint application of morphactin no. 1 and herbicides U-46 KV Pulver, Pielik and Sys 67-Prop.